Association between oxidative balance score and neck circumference in Korean adults. Issue 4 (July 2022) - Yeo, Jina; Hwang, In Cheol; Ahn, Hong Yup
Abstract: The relationship between oxidative stress and central obesity is contradictory. Here, we investigated the association between oxidative balance (OB) score and neck circumference (NC). Data obtained from the 2019 to 2020 Korean National Health and Nutrition Examination Surveys were analyzed for 5807 adults with available OB scores and NCs. Multivariate regression models adjusted for potential confounders including demographics, comorbidities, and total energy intake revealed that subjects with a higher OB score had a significantly smaller NC in men and women. Our results indicate that oxidative imbalance indicates the presence of central obesity.